2009
DOI: 10.1172/jci35814
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+/calmodulin-dependent kinase II triggers cell membrane injury by inducing complement factor B gene expression in the mouse heart

Abstract: Myocardial Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) inhibition improves cardiac function following myocardial infarction (MI), but the CaMKII-dependent pathways that participate in myocardial stress responses are incompletely understood. To address this issue, we sought to determine the transcriptional consequences of myocardial CaMKII inhibition after MI. We performed gene expression profiling in mouse hearts with cardiomyocyte-delimited transgenic expression of either a CaMKII inhibitory peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
154
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(163 citation statements)
references
References 64 publications
(58 reference statements)
8
154
0
1
Order By: Relevance
“…Conversely, C5a-receptor deficiency in a murine knock-out model has been associated with decreased resistance to cardiac stress, underscoring that complement might act as a double-edged sword also in the heart (Mullick et al, 2011). The mechanisms for in situ increased complement activation in heart failure are currently unknown, but myocardial levels of complement factor B are upregulated after myocardial infarction through toll-like receptor signaling and inflammatory cytokines (Singh et al, 2009;Singh et al, 2012). Complement factor B deficient mice subjected to myocardial infarction have improved survival and cardiac function, less cardiac hypertrophy, and importantly, markedly reduced myocardial C3 deposition.…”
Section: Pathogenic Role Of Complement In Heart Failure Developmentmentioning
confidence: 99%
“…Conversely, C5a-receptor deficiency in a murine knock-out model has been associated with decreased resistance to cardiac stress, underscoring that complement might act as a double-edged sword also in the heart (Mullick et al, 2011). The mechanisms for in situ increased complement activation in heart failure are currently unknown, but myocardial levels of complement factor B are upregulated after myocardial infarction through toll-like receptor signaling and inflammatory cytokines (Singh et al, 2009;Singh et al, 2012). Complement factor B deficient mice subjected to myocardial infarction have improved survival and cardiac function, less cardiac hypertrophy, and importantly, markedly reduced myocardial C3 deposition.…”
Section: Pathogenic Role Of Complement In Heart Failure Developmentmentioning
confidence: 99%
“…It has been previously demonstrated that factor B is upregulated 3 wks after myocardial infarction in a murine model (22). We have observed that factor B is upregulated in hearts that underwent cold I/R compared with control hearts in a syngeneic, heterotopic cardiac transplant model (Supplementary Figure S1).…”
Section: Factor B Is Upregulated Early After Myocardial I/rmentioning
confidence: 62%
“…More recently, it has been shown that local production of factor B is markedly upregulated in a murine myocardial infarction model. In the same study, factor B -/-mice demonstrated less myocardial complement deposition and less adverse remodeling after ischemic myocardial injury (22). In aggregate, these observations highlight the importance of factor B in local tissue damage caused by autoimmunity and demonstrate that local production of factor B is important to the pathogenesis of ischemic tissue injury as well.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…NF-κB was first identified as a transcription factor of immunoglobulin κ light chain in B cells and is characterized by its important roles in the immune system [4] . NF-κB is now known to be ubiquitously expressed in all cell types and has prominent roles in tumorigenesis and the development of neural, heart and immune diseases [4][5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%